Green preparation of high-yield and large-size hydrophilic boron nitride nanosheets by tannic acid-assisted aqueous ball milling for thermal management. (January 2023) - Wu, Ni; Yang, Wang; Che, Sai; Sun, Li; Li, Huawei; Ma, Guang; Sun, Yankun; Liu, Hongchen; Wang, Xiaobai; Li, Yongfeng
Graphical abstract: Highlights: Tannic acid (TA)-assisted aqueous ball milling was firstly used to massively fabricate hydrophilic BNNS. As-prepared ultrathin BNNS-TA exhibited high yield, high concentration, and relatively large lateral size. TA functionalization improved the dispersion and interfacial compatibility of BNNS-TA in epoxy matrix. Thermal management capability and mechanical properties of BNNS-TA/epoxy composite were concurrently enhanced. Abstract: The thermal management application of boron nitride nanosheet (BNNS) is restricted by the low-yield exfoliation techniques and poor dispersibility. In this work, we develop a controllable ball milling approach with the addition of biocompatible tannic acid (TA) to achieve the exfoliated and hydrophilic TA-modified BNNS (BNNS-TA). This method features the advantages of high yield (60 %), large lateral size (∼3.4 μm), and excellent water solubility (40 mg/mL). The BNNS-TA is further incorporated with epoxy resin to fabricate thermal management materials with remarkable thermal and mechanical performance. The thermal conductivity of BNNS-TA/epoxy composite reaches 2.3 W/mK at 40 wt% loading, which is 12.8 and 1.8 times of that for pure epoxy and unmodified BNNS/epoxy composite, showing superior heat dissipation capability than the commercial thermal pad when applied in LED chips. Additionally, the BNNS-TA/epoxy composite also exhibits enhanced mechanical strength thanks to the improved dispersion and reinforced interfacial interactions.